Technical Efficiency of Battery Cage and Deep Litter Systems in Poultry Production - Ajiboye , B.O.; Bamiro, O.M.; Adeyonu, A.G.; Faseyi, S.A. (International Journal of Poultry Science, 2019)
Background and Objective: The importance of the poultry industry to the national economy cannot be overemphasized. Approximately 10% of the Nigerian population is engaged in poultry production, mostly on subsistence and small or medium-sized farms. However, the output level still remains low compared to the input. The aim of this study was to examine the technical efficiency of the battery cage and deep litter systems of poultry production in Nigeria. Materials and Methods: A multi-stage sampling technique was used to select 120 battery cage farmers and 120 deep litter farmers. A well-structured questionnaire was used to collect information on the farmers and the farm characteristics. The data collected were analysed using descriptive and inferential statistics. Results: The budgetary analysis showed that the net profit for one bird for the battery cage farmer stood at ₦587, whereas that of the deep litter farmer was ₦635. Stochastic frontier modelling showed a higher inefficiency in the deep litter system of poultry production compared with the battery cage system. The efficiencies were 79 and 60% for the battery cage and deep litter farms, respectively. Additionally, labour and flock size contributed to the inefficiencies of both the battery and deep systems of poultry production. The Chow test (Fcal = 0.45 and Ftab = 2.3) showed that there was no structural difference in the production of the battery cage and deep litter systems in the study area. Conclusion: The results show that even though the two systems are profitable but the battery cage system is more profitable than the deep litter system.